2007
DOI: 10.4081/jlimnol.2007.s1.40
|View full text |Cite
|
Sign up to set email alerts
|

Three new species of Macrobiotus (Eutardigrada, Macrobiotidae, tenuis-group) from Tien Shan (Kirghizia) and Spitsbergen

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 3 publications
0
23
0
1
Order By: Relevance
“…(e.g. Binda et al 1980, Coulson et al, 2014Dastych 1983Dastych , 1985De Smet and van Rompu 1994;Beyens 1987, 1988;Janiec 1996;Kaczmarek et al 2012;Opalinski 1986, 1989;Maucci 1996;Mokievsky 1992;Pilato et al, 1982;Pilato and Binda 1987;Smykla et al 2011;Tumanov 2007;Van Rompu and De Smet 1988Jankovská et al, 2016;Vonnahme et al, 2016;Zawierucha 2013;Zawierucha et al, 2013Zawierucha et al, , 2015a2016a,b,c,d;.…”
Section: Heterotardigrada Echiniscidaeunclassified
See 1 more Smart Citation
“…(e.g. Binda et al 1980, Coulson et al, 2014Dastych 1983Dastych , 1985De Smet and van Rompu 1994;Beyens 1987, 1988;Janiec 1996;Kaczmarek et al 2012;Opalinski 1986, 1989;Maucci 1996;Mokievsky 1992;Pilato et al, 1982;Pilato and Binda 1987;Smykla et al 2011;Tumanov 2007;Van Rompu and De Smet 1988Jankovská et al, 2016;Vonnahme et al, 2016;Zawierucha 2013;Zawierucha et al, 2013Zawierucha et al, , 2015a2016a,b,c,d;.…”
Section: Heterotardigrada Echiniscidaeunclassified
“…Studies of tardgrades from limnic biotopes have hitherto been scarcely reported. Mihelčič (1971Mihelčič ( , 1971Mihelčič ( /1972 Maucci (1975, 1979) Mihelčič, 1971/1972 Mesobiotus harmsworthi harmsworthi Prins Karls Forland (Svalbard) Franz Josef Land (Russia) Mesobiotus harmsworthi obscurus (Dastych, 1985) Hornsund; Albert I Land; Andreé Land; Atomfjella (Svalbard) Paramacrobiotus areolatus Prins Karls Forland (Svalbard) Franz Josef Land (Russia) Tenuibiotus voronkovi (Tumanov, 2007) Kongsfjorden (Svalbard)…”
Section: Methodsmentioning
confidence: 99%
“…Richters 1911), new tardigrades are still being discovered in both the Arctic and the Antarctic (e.g. Miller et al 2005;Tumanov 2007;McInnes 2010;Dastych 2011;Kaczmarek et al 2012;Kaczmarek et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Other papers were published sporadically, and the majority were limited to reports and descriptions of new species from the Svalbard Archipelago (e.g. Binda et al 1980;Pilato et al 1982;Dastych 1983;De Smet et al 1987Pilato and Binda 1987;Van Rompu and De Smet 1988, 1991, 1994De Smet and Van Rompu 1994;Maucci 1996;Tumanov 2007;Smykla et al 2011). In the region of Hornsund, studies were previously conducted by Węglarska (1965), Dastych (1985), Maucci (1996), Janiec (1996) and Łagisz (1999).…”
Section: Introductionmentioning
confidence: 99%